Volvulus with bowel necrosis after laparoscopic appendectomy. Migration of Clip? - Kakaty, Diganta (J Surg Case Rep, 2018)
About 2.8% of patients develop small bowel obstruction, mostly following an open approach appendectomy. Case Report: we present an 18-year-old girl with acute abdomen 10 days following laparoscopic appendectomy. An emergency laparotomy was performed which revealed bowel necrosis and an impacted slipped clip on the mesenterial side of the bowel with signs of bowel strangulation and necrosis. Bowel resection was carried out with primary enteroenteric anastomosis. We suspect the sharp ends of the open clip allowed it to become lodged in the bowel segment resulting in bowel obstruction and subsequent necrosis. It is possible that the clip migrated or was a failed deployment. To our knowledge, this is the first report of mechanical bowel obstruction after laparoscopic appendectomy caused by aberrant surgical clip.